Control of Internal Moisture Transfer Direction and Lateral Moisturization to Mitigate Drying Defects in Large-Cross Section Timber - Bat-Uchral Batjargal; Taekyeong Lee; Chang-Jin Lee; Jung-Kwon Oh; Hwanmyeong Yeo (BioResources)
Methods for surface moisturization and control of internal moisture movement have been developed to minimize moisture gradients and reduce drying defects, such as cracks, in large cross-sectional timbers used for restoring palaces, temples, and cultural heritage buildings. Cross-sectional sealing and steaming pre-treatments were applied before kiln drying to regulate the internal moisture transfer. Real-time weight changes were monitored using a load cell to track the average moisture content, and hygrometers were used to estimate the moisture content at various positions within the wood. The experimental results demonstrated that the cross-sectional coating with lateral moisturization effectively reduced drying defects, thereby contributing to the preservation of wooden cultural heritage sites and enhancing the sustainability of timber resources. The total drying duration was 835.4 h (approximately 35 d), confirming that surface moisturization is critical in minimizing defects during drying.